2008
DOI: 10.1007/s10714-008-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative closed Friedman universe

Abstract: Heller et al. (J Math Phys 46:122501, 2005; Int J Theor Phys 46:2494, 2007 proposed a model unifying general relativity and quantum mechanics based on a noncommutative algebra A defined on a groupoid having the frame bundle over spacetime as its base space. The generalized Einstein equation is assumed in the form of the eigenvalue equation of the Einstein operator on a module of derivations of the algebra A. No matter sources are assumed. The closed Friedman world model, when computed in this formalism, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mathematical aspects of the model were dealt with in [21], and its physical content in [22]. Details of the Friedman cosmological model were computed in [11,24]. Further works, especially regarding field theoretical and observational aspects of the model, are in progress.…”
Section: The Model and Its Motivationmentioning
confidence: 99%
“…Mathematical aspects of the model were dealt with in [21], and its physical content in [22]. Details of the Friedman cosmological model were computed in [11,24]. Further works, especially regarding field theoretical and observational aspects of the model, are in progress.…”
Section: The Model and Its Motivationmentioning
confidence: 99%
“…In [3], we have shown that, for the closed Friedman model, the normal states on the von Neumann algebra M (restricted to M 0 ), are of the form…”
Section: Noncommutative Geometry Of the Closed Friedman Modelmentioning
confidence: 99%
“…The present paper is mainly based on reference [3]. Here I give only a rather sketchy presentation of our model, for technical details referring the reader to our original papers, my intention being to focus on the above signaled conceptual problems.…”
Section: Introductionmentioning
confidence: 99%